2023
DOI: 10.1002/jcu.23545
|View full text |Cite
|
Sign up to set email alerts
|

Brain injury mobile diagnostic system: Applications in civilian medical service and on the battlefield—General concept and medical aspects

Radosław Kaźmierski

Abstract: To present the concept of a portable ultrasound tomography device for diagnosing traumatic and vascular brain lesions. The device consisting of multiple transcranial ultrasound probes placed on the surface of the head, specifically but not exclusively in natural acoustic windows. An integral part of the mobile diagnostic system (MDS) is a decision support system based on artificial intelligence algorithms utilizing information from: head images, laboratory data, and assessment of the patient's clinical conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…The MIST trial demonstrated that the use of a MIST was faster and led to improved discharge outcomes when compared with the drip-and-ship model, i.e., transporting the patient to the nearest primary stroke center [139]. Another novel concept is a portable ultrasound tomography device for vascular brain lesions proposed by Kazmierski [140]. This device contains multiple transcranial ultrasound probes placed on the surface of the head allowing for a significant reduction in time from stroke onset to thrombolytic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The MIST trial demonstrated that the use of a MIST was faster and led to improved discharge outcomes when compared with the drip-and-ship model, i.e., transporting the patient to the nearest primary stroke center [139]. Another novel concept is a portable ultrasound tomography device for vascular brain lesions proposed by Kazmierski [140]. This device contains multiple transcranial ultrasound probes placed on the surface of the head allowing for a significant reduction in time from stroke onset to thrombolytic therapy.…”
Section: Discussionmentioning
confidence: 99%